AUDIT MANAJEMEN ATAS SISTEM BAGI HASIL PADA PT.BNI SYARIAH MAKASSAR - sri, megawati; Putra, Trisno Wardy (Universitas Muhammadiyah Makassar, 2019)
This study aims to determine the management audit of the revenue sharing system at PT. BNI Syariah Makassar. This research uses quantitative descriptive method where company data regarding management audit of financing and profit sharing systems and other data supporting research is collected and then the data is described and whether it is in accordance with PSAK 105 concerning Mudharabah Accounting. The object of the research is PT.BNI Syariah Makassar. The results of the study show that BNI Syariah Makassar is not fully in accordance with PSAK 105, because there are differences in terms of the distribution of business profits where BNI Syariah still uses the principle of revenue sharing while in PSAK 105 uses the principle of profit sharing or profit sharing.